Особливості функціонування невербальних комунікативних компонентів у ситуації поздоровлення - Мудрик, Лариса Валентинівна; Mudryk, L. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто функціонально-прагматичні особливості невербальних засобів, що вживаються на позначення поздоровлення в сучасній англійській мові. Виділено найуживаніші невербальні комунікативні компоненти в ситуації поздоровлення, а також розкрито їхній прагматичний потенціал. Встановлено, що найбільш ефективними номінаціями невербальних засобів на позначення поздоровлення є кінесичні (міміко-жестові компоненти), такесичні та просодичні. The article deals with the functional and pragmatic peculiarities of the nonverbal means used for designating congratulations in modern English. It is emphasized that nonverbal communicative components of the congratulatory situation are characterized by originality of their functioning and specificity of their pragmatic function. The most common nonverbal communicative components in the congratulatory situation are singled out and their pragmatic potential is revealed. It has been ascertained that the most effective nominations of the nonverbal means used for designating congratulations are kinesic (facial expression and body gesture components), tactile and prosodic.
Functional Peculiarities of Nonverbal Communicative Components in the Congratulatory Situation
Keywords: невербальні комунікативні компоненти; nonverbal communicative components; кінетика; kinesics; просодія; prosody